The influence of financial attitude, behaviour and knowledge on financial literacy: a Malaysian perspective / Amira Rosalia Aripin - Aripin, Amira Rosalia (2019)
Financial Literacy among youths is a global concern worldwide. This includes alarming problems such as the high bankruptcy level among youths and the weaknesses in managing finance among youths such as managing debt, personal finance and savings. The GECD has provided a framework which assess the Financial Attitude, Financial Behaviour and Financial Knowledge to determine the level of Financial Literacy among youths. However, the result will very much vary within countries such as first world countries like UK, Canada, and Germany and third world countries like India, Bangladesh and Vietnam. Thus it is significant to carry out the study in Malaysia. This study has been conducted among 220 youths with purposive sampling method. It uses primary data which is derived from questionnaires that have been distributed to individuals from different field of expertise and working fields. Secondary data are also used to help researcher in getting a clearer picture of the situation on a global perspective. The definition of youths in the Malaysian context refers to those 30 years old and below. The time frame of conducting the study is within the year 2019 and it is not time significant. The result has shown that between the variables 'Financial Knowledge' is the most significant in determining the level of financial literacy among youths in Malaysia. However, there are some limitations in the study such as the sample size, the scope of variable used and medium to collect the data.